(untitled) (Journal of the College of Basic Education, 2022)
In order to achieve the objective of the research and to test hypotheses, the researcher used the analytical descriptive research method. The researcher prepared a test to measure the skills of mathematical thinking damaged from (27) The researcher realized the validity of the internal consistency of the test and its values ​​ranged between (0.45 - 0.83) and a stability of (87%). The researcher prepared the following six thinking skills: (induction, conclusion, survey, Test in educational statistics to measure The academic achievement consists of (21) paragraphs of multiple choice, ranging between (32.0 - 74.0) and a stability of (89%). After applying the test to the sample of 200 students from the second stage in mathematics department, and processing the data statistically, the researcher reached the following results: 1- Students of the College of Basic Education have the second stage (research sample) skills of thinking in mathematics but at a level below the acceptable level of performance. 2- There is a positive correlation between the six mathematical thinking skills, each with each other, and between each skill with the total score of the test. 3- There is a positive correlation between each skill of the six mathematical thinking skills in mathematics as well as the total score of the test with the academic achievement of the students in the research sample. The mathematical thinking skills affect the academic achievement. 4- There are no differences in the correlation between the skills of mathematical thinking and achievement in the study of statistics attributed to the gender variable.